2021
DOI: 10.3390/ani11082224
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hydrated Aluminosilicates Supplemented in Litter and Feed on Chicken Growth, Muscle Traits and Gene Expression in the Intestinal Mucosa

Abstract: The aim of the study was to compare the production, muscle traits and gene expression in the intestinal mucosa of chickens supplemented with aluminosilicates in feed and litter simultaneously. A total of 300 Ross 308 were maintained for 42 days. Group 1 was the control group. In group 2, 0.650 kg/m2 of halloysite was added to the litter and 0.5–2% to the feed (halloysite and zeolite in a 1:1 ratio); in group 3, we added zeolite (0.650 kg/m2) to the litter and 0.5–2% to the feed. The production parameters, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Nevertheless, when discussing the effect of bedding, the combined supplementation system and adding bioactive substances to the litter material is worth mentioning. For example, aluminosilicates as a feed additive and litter have a positive local immunomodulating effect in GALT and are beneficial in broiler performance ( Biesek et al, 2021b ).…”
Section: Shaping the Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, when discussing the effect of bedding, the combined supplementation system and adding bioactive substances to the litter material is worth mentioning. For example, aluminosilicates as a feed additive and litter have a positive local immunomodulating effect in GALT and are beneficial in broiler performance ( Biesek et al, 2021b ).…”
Section: Shaping the Immune Responsementioning
confidence: 99%
“…Previous studies on using aluminosilicates in poultry production confirmed their effect as a feed or bedding additive on production results, slaughter yield, meat quality, and intestinal morphology ( Banaszak et al, 2020 , 2021a , 2022b ; Biesek et al, 2021a ). Aluminosilicates also affect the expression of intestinal mucosa genes in the context of supporting health status ( Biesek et al, 2021b ; Dunislawska et al, 2022 ).…”
Section: Pathways Of Immunostimulation and Immunomodulationmentioning
confidence: 99%
“…Chickens usually live on chicken litter, which is composed of various waste products such as their own feces and feathers (Biesek et al, 2021). Ammonia emissions from chicken litter produce strong smells, due to ammonia volatilization and poor air quality, which can harm the physical and mental health, as well as the overall well-being of chickens and poultry workers (Biesek et al, 2021). The presence of substantial amounts of ammonia in the litter can also directly harm the chickens who must live and walk on their own feces.…”
Section: Impacts On Non-human Animal Healthmentioning
confidence: 99%
“…The presence of substantial amounts of ammonia in the litter can also directly harm the chickens who must live and walk on their own feces. For example, elevated levels of ammonia in the chicken's living environment can lead to footpad dermatitis due to increased pH levels, harming the chicken's well-being as lesions form on the chicken's feet and increase the risk of infection (Biesek et al, 2021).…”
Section: Impacts On Non-human Animal Healthmentioning
confidence: 99%
“…In addition, they can favourably influence production outcomes and animal health [9]. Added to bedding, they improve the microclimate of animal housing owing to their drying properties and capacity to reduce the amount of gases released, thus favourably influencing animal welfare [10]. These additives are safe in the amount of 0.2-1% of a commercial diet for broilers or pigs and have no negative effect on production, even improving poultry productivity [11].…”
Section: Introductionmentioning
confidence: 99%